THE SESSIONAL AVAILABILITY AND SOCIO-ECONOMIC IMPORTANCE OF BEE FLORA OF DISTRICT BAJAUR, PAKISTAN - Hayat Ullah; Fazal Hadi; Taqiur Rahman; Sami Ullah (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Bees forage plants and honey bees play a significant role in agriculture, environment and economy Pakistan. The Bee Flora Calendar, which outlines the flowering periods of key plants which is crucial for honey production in District Bajaur. Among the major beekeeping hotspots in the region, the natural forests of Tehsil Mamund, Tehsil Barang, and Tehsil Salarzai provide essential forage resources for honeybee populations, supporting sustainable apiculture and local livelihoods. The study was carried out to assess the Bee flora and flowering calendar that produce maximum honey following the flowering period of the local bee flora. The Semi structured questionnaires, participatory Rural Appraising techniques, and field observation were utilized for the collection of data. During the field survey a total of (82) plant species (Table 1) of Bee flora were identified and also enlisted with their flowering period and potential point areas. The field survey shows the socio-economic importance ofbeekeeping and Production of Honey and Net Income from Honey of the local Beekeepers. The overall total average production of honey and the net income per beekeeper net cost from honey production were 840kg per year. The results in Table.3 show that the highest average annual production were recorded from Tehsil Salarzai (180 kg) followed by Tehsil Barang (160 kg), Tehsil Mamund (160 kg), Tehsil Chamar kand (140 kg) and Tehsil Utman Kail (80 kg) which is the lowest production were documented in district Bajaur the total average cost on the Honey Bees is (340,000PKR) and the Total annual Net Income from honey sell is (1,334,000 PKR) (700 kg). The total annual cost was observed in this study (70000 Rs.), the highest cost was recorded in Tehsil Salar Zai and Barang followed by (50000 Rs.), while the minimum annual cost of beekeepers was recorded from Tehsil Salar Zai regarding the net Honey Production (7000 Rs.). The total average gross annual income from honey sale was recorded is (1,512,000 PKR). In this regard the Beekeeping industry having a key role in the income of local community.